Analisis Kemampuan Pemecahan Masalah Matematis Siswa Dalam Menyelesaikan Soal Higher Order Thinking Skills (HOTS) Pada Materi Persamaan Garis Lurus - Ali Auliarahmah, Resma; Tia Yulyarianti, Eneng; Sugilar, Hamdan (UIN Sunan Gunung Djati Bandung, 2025)
The purpose of this study was to channel students' ability to solve mathematical problems, especially those related to linear equations and dependent on Higher Order Thinking Skills (HOTS). With 18 students as research subjects in one of the junior high schools in Bandung Regency, a quantitative descriptive method was used. Understanding the problem, planning a solution strategy, implementing the plan, and re-checking the solution are Polya's problem-solving indicators used to collect data. The results showed that most students still failed to re-check and plan a solution strategy. In addition, there was a significant variation in ability among students, with most being in the medium and low ability categories. The problems faced by students included failure to systematically submit concepts when planning strategies and lack of thoroughness in re-checking answers to ensure their correctness. Therefore, a more effective learning approach is needed with a focus on strengthening critical thinking and problem-solving skills through HOTS practice questions.